The noninvasive assessment of maxillary sinus - Munjal, Manish; Gupta, Ritu; Rishi, Porshia; Goyal, Ajay; Munjal, Shubham; Garg, Shubham; Singh, Archit Pal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The maxillary sinus with its antigravity drainage affected by pathology at the osteomeatal unit, necessitates an intervention, medical or surgical. Role of basic imaging in pretreatment evaluation is elaborated upon.